Do Markets (Institutions) Drive Out Lemmings or Vice Versa? - Andrea Morone; Simone Nuzzo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We investigate, by mean of a lab experiment, a market inspired by two strands of literature on one hand we have herd behaviour in non-market situations, and on the other hand aggregation of private information in markets. The former suggests that socially undesirable herd behaviour may result when information is private; the latter suggests that socially undesirable behaviour may be eliminated through the market. As the trading mechanism might be a compounding factor, we investigate two kinds of market mechanism: the double auction, where bids, asks and trades take place in continuous time throughout a trading period; and the clearing house, where bids and asks are placed once in a trading period, and which are then cleared by an aggregating device. As a main result, this paper shows that double auction markets are, in several instances, superior to clearing house markets in terms of informational efficiency. Moreover, the employed trading institutions do not exhibit significant differences in both market volume and price volatility.
Keywords: C91; D02; G14; 330; Experimental Markets; Market Efficiency; Double Auction; Clearing House